Pinus patula var. longepedunculata Loock growth in plantations of the Sierra Sur of Oaxaca - Pedro Cruz, Adrián; Galán Larrea, Rolando; de los Santos Posadas, Héctor M.; Valera Venegas, Gricelda; Rivera Nava, Juana Laura; Sandoval García, Celestino (Instituto de Ecología, A.C., 2022)
The research works on growth and yield of forest plantations, particularly in coniferous species planted in the different Mexican tropical regions, are scarce. Mathematical models are a useful tool for optimal timber forest resources management. In this work, whole stand explicit prediction models were fitted, with data from permanent plots, to determine the growth and timber yields of forest plantations of Pinus patula var. longepedunculata Loock in the Sierra Sur of Oaxaca. Site index was determined with the polymorphic Schumacher model, which was correlated with the basal area and volume models through seemingly unrelated regression. Families of curves with site indexes of 9 m, 11 m, 13 m and 15 m for height at a base age of 10 years were obtained; in basal area site indexes of 32.9 m2 ha-1, 37.9 m2 ha-1, 42.5 m2 ha-1 and 47 m2 ha-1 at 20 years of age were estimated. In addition, a volume per site indexes of 187.5 m3 ha-1, 234.3 m3 ha-1, 282 m3 ha-1 and 330.6 m3 ha-1 was determined at this latter age. The maximum yield obtained for each site was 10.23 m3 ha-1 year-1, 12.04 m3 ha-1 year-1, 14.12 m3 ha-1 year-1, 16.6 m3 ha-1 yr-1, which suggests rotation periods differents for each site ranging from 19 years to 30 years time.